Bounded geometry for p-homeomorphisms on the circle with critical point: Bounded geometry for p-homeomorphisms on the circle with critical point - Safarov , Utkir (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
We consider an orientation preserving circle homeomorphism that rotation number is